Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
S = 3 + 3² + 3³ + ... + 3⁹⁹ + 3¹⁰⁰
= 3 + (3² + 3³ + 3⁴) + (3⁵ + 3⁶ + 3⁷) + ... + (3⁹⁸ + 3⁹⁹ + 3¹⁰⁰)
= 3 + 3².(1 + 3 + 3²) + 3⁵.(1 + 3 + 3²) + ... + 3⁹⁸.(1 + 3 + 3²)
= 3 + 3².13 + 3⁵.13 + ... + 3⁹⁸.13
= 3 + 13.(3² + 3⁵ + ... + 3⁹⁸)
Do 13.(3² + 3⁵ + ... + 3⁹⁸) ⋮ 13
⇒ 3 + 13.(3² + 3⁵ + ... + 98) chia 13 dư 3
Vậy S chia 13 dư 3
\(a,S=1+3+3^2+....+3^{100}.\)
\(\Rightarrow3S=3+3^2+...+3^{101}\)
\(\Rightarrow3S-S=\left(3+3^2+...+3^{101}\right)-\left(1+3+....+3^{100}\right)\)
\(\Rightarrow2S=3^{101}-1\)
\(\Rightarrow S=\frac{3^{101}-1}{2}\)
\(b,A=1+3^2+3^4+...+3^{100}\)
\(\Rightarrow3^2A=3^2+3^4+...+3^{102}\)
\(\Rightarrow9A-A=\left(3^2+3^4+...+3^{102}\right)-\left(1+3^2+....+3^{100}\right)\)
\(\Rightarrow8A=3^{102}-1\)
\(\Rightarrow A=\frac{3^{102}-1}{8}\)
a) S=\(1-3+3^2-3^3+...+3^{98}-3^{99}.\)
=\((1-3+3^2-3^3)+...+3^{96}-3^{97}+3^{98}-3^{99}.\)
=\(\left(1-3+3^2-3^3\right)+..+3^{96}\left(1-3+3^2-3^3\right)\)
=(\(1-3+3^2-3^3\))(1+\(3^4+...+3^{92}+3^{96})\)
=-20(1+\(3^4+...+3^{92}+3^{96})\)là bội của -20
A = 3 + 32 + 33 + ... + 3100
⇔ 3A = 3( 3 + 32 + 33 + ... + 3100 )
⇔ 3A = 32 + 33 + ... + 3101
⇔ 2A = 3A - A
= 32 + 33 + ... + 3101 - ( 3 + 32 + 33 + ... + 3100 )
= 32 + 33 + ... + 3101 - 3 - 32 - 33 - ... - 3100
= 3101 - 3
2A + 3 = 3x+100
⇔ 3101 - 3 + 3 = 3x+100
⇔ 3101 = 3x+100
⇔ 101 = x + 100
⇔ x = 1
Vậy x = 1
S = 3 + 32 + 33 + ... + 3100
3S = 32 + 33 + 34 + ... + 3101
3S - S = ( 32 + 33 + 34 + ... + 3101 ) - ( 3 + 32 + 33 + ... + 3100 )
2S = 3101 - 3
S = \(\dfrac{3^{101}-3}{2}\)